2009
DOI: 10.1002/ijc.24446
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 gene polymorphisms and esophageal squamous cell carcinoma risk in Chinese population: A meta‐analysis of case–control studies

Abstract: Two non-synonymous polymorphisms Arg194Trp and Arg399Gln in the DNA-base excision repair gene X-ray repair cross-complementing group 1 (XRCC1) have been implicated in risk for esophageal cancer. However, the results from different studies remain controversial. The present meta-analysis of literatures was performed to clarify these associations in Chinese population. A comprehensive literature search was conducted to identify all case-control studies of XRCC1 polymorphisms Arg194Trp and Arg399Gln and risk for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…Our analysis also demonstrated that the XRCC1 Gln399 allele elevated risk of ESCC in Chinese, which is inconsistent with the study of Dai et al (2009). The different results may be due to the studies performed in the last 3 years and included in our meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Our analysis also demonstrated that the XRCC1 Gln399 allele elevated risk of ESCC in Chinese, which is inconsistent with the study of Dai et al (2009). The different results may be due to the studies performed in the last 3 years and included in our meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…The DNA repair protein XRCC1 interacted with enzymatic components which include PARP-1, DNA polymerase β, APE1, PNK, PCNA and DNA ligase III in BER pathway [14-19]. Single nucleotide polymorphisms (SNPs) of XRCC1 gene acted as a risk factor might be a valuable genetic marker for chemotherapy in various cancers containing esophageal cancer [20-22]. Our group has demonstrated the possibility of JWA participating in tailored therapy of tumor for its novel function as regulator of XRCC1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many investigators have reported association between CYP1A1 polymorphisms and cancers (Dai et al, 2009;Atinkaya et al, 2012;Lopez-Cima et al, 2012;Sergentanis et al, 2012;Ding et al, 2013), especially for two main functional polymorphic sites of CYP1A1 gene (MspI and Ile/Val) and cancer susceptibility. Previous studies (Kawajiri et al, 1990;Nakachi et al, 1991;Hayashi et al, 1992;Xu et al, 1996) have suggested that variant allele of CYP1A1 MspI polymorphisms is associated with malignancies, particularly lung cancer.…”
Section: Introductionmentioning
confidence: 99%